2017
DOI: 10.1007/s11095-017-2098-2
|View full text |Cite
|
Sign up to set email alerts
|

Revealing pMDI Spray Initial Conditions: Flashing, Atomisation and the Effect of Ethanol

Abstract: Vapour generation in pMDIs occurs upstream of the sump, and the dominant volume component in the nozzle exit orifice is vapour at all times in the injection. The flow in ethanol-containing pMDIs has a bubbly structure resulting in a comparatively stable discharge, whereas the binary structure of propellant-only flows results in unsteady discharge and the production of unrespirable liquid masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Visualization of MDI actuation and aerosol formation has been attempted by using high-speed camera, laser diffraction, Schlieren optical imaging, and phase-contrast X-ray imaging [31][32][33][34][35][36][37]. With a laser and high-speed camera, Smyth et al observed asymmetrical and ellipsoid spray cross-sections in the vertical direction [38].…”
Section: Introductionmentioning
confidence: 99%
“…Visualization of MDI actuation and aerosol formation has been attempted by using high-speed camera, laser diffraction, Schlieren optical imaging, and phase-contrast X-ray imaging [31][32][33][34][35][36][37]. With a laser and high-speed camera, Smyth et al observed asymmetrical and ellipsoid spray cross-sections in the vertical direction [38].…”
Section: Introductionmentioning
confidence: 99%
“…In this mechanism, the propellant rapidly expands and undergoes flash evaporation, resulting in the formulation forming a two-phase flow [ 2 , 11 ]. During the swift, subsequent expulsion from the actuator, the remaining liquefied component is dispersed into droplets through shear forces [ 10 , 12 ], and the initial droplets undergo further processes of evaporation (also known as droplet ‘ageing’). The resultant size of this initial droplet distribution has long been shown to be dependent on the formulation characteristics (such as viscosity, surface tension and non-volatile solute concentration) and device design [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The propensity of a flow to cavitate, but not the form the cavitation takes, is generally assessed by its cavitation number, which can be determined directly from the vapour phase properties of the liquid and its operating pressure [28]. To obtain the phase state, distribution techniques such as phase contrast imaging and X-ray radiography can be used [7,33]. Phase contrast imaging provides internal and external visualization of vapour and liquid distributions, whereas X-ray radiography provides quantification of the mass distribution from which phase state can be determined, although this approach is limited to the nozzle's external flow.…”
Section: Introductionmentioning
confidence: 99%